(untitled) (Development Service Industry Management, 2025)
The article examines the theoretical and methodological foundations of human capital development under digital transformation and the security challenges caused by the war against Ukraine. The study substantiates the growing importance of digital technologies and competencies as key determinants of human capital value, economic competitiveness, and systemic resilience. It is demonstrated that global digitalisation, the rapid advancement of AI technologies, and shifts in global markets drive the need to rethink mechanisms for developing intellectual potential, addressing demographic and investment gaps, and modernising educational and research infrastructures. Contemporary scientific approaches to human capital formation — including competency-based, innovative, and digitalisation-oriented concepts — are analysed. The research identifies major challenges: labour force losses due to migration and military actions, insufficient investment in R&D, imbalances between labour market needs and educational systems, low commercialisation of research, and the increasing demand for digital skills. A structural approach is proposed to identify digital innovations that influence the security, competitiveness, and sustainable development of enterprises and the national economy. A mechanism for ensuring the effectiveness of intellectual capital development is developed, encompassing managerial, institutional, regulatory, and methodological subsystems, and outlining conditions for implementing intellectual and innovative potential within economic processes. The study concludes that digital intellectualisation of human capital fosters the creation of new competencies, enhances the resilience of economic systems, and supports the restoration and strengthening of the competitive positions of Ukrainian enterprises.